STABILIZING MUSCLES OF THE LUMBAR SPINE STRENGTHENING IN THE TREATMENT OF LOW BACK PAIN (Fiep Bulletin - online, 2012)
Background: The high prevalence in the population and the significant negative social and economic impact generated by the cases of disability justify the importance of the study of low back pain. Objective: Evaluate the effect of an exercise protocol to strengthen the stabilizing muscles of the lumbar spine in the treatment of low back pain. Methods: The proposed protocol was applied in 15 subjects randomly assigned to two groups, treated (TG) and a control group (CG), aged between 20 and 60. Methods of assessment questionnaires were used to McGill and Roland-Morris and stabilizer pressure biofeedback unit. The TG was submitted to an exercise protocol, based on the segmental stabilization, which emphasizes the strengthening of the transversus abdominis muscle. The CG did not receive the intervention. Results and conclusion: The results were that the TG presented significant improvement of lumbar function, the transverse abdominal muscle activation (both p
Keywords: low back pain; exercise therapy; physical therapy.